The myth: in vivo degradation of polypropylene-based meshes. (February 2017) - Thames, Shelby; White, Joshua; Ong, Kevin
Abstract Introduction and hypothesis Polypropylene is a base polymer used in biomaterial applications, including sutures and mesh products, for the treatment of pelvic organ prolapse, stress urinary incontinence, and hernia repairs. Previous studies have dismissed the value of formulation additives employed in polypropylene, and the importance and necessity of an effective mesh explant cleaning protocol when characterizing explanted devices. However, both are critical to understanding the alleged degradation of polypropylene-based meshes. Methods An effective, nondestructive, hydrolytic cleaning process, supplemented with light microscopy (LM), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) data, was used to evaluate 78 explanted Prolene meshes (with duration of implantation ranging from 0.4 to 11.7 years). Results The cleaning process exposed clean, unoxidized, nondegraded Prolene fibers with smooth surfaces and with no visible evidence of gradient-type or ductile damage. LM showed identical translucent and sometimes clear, cracked/flaking material on both blue and clear fibers, instead of clear cracked/flaking material on the clear fibers and blue cracked/flaking material on the blue fibers. FTIR confirmed progressive protein removal and loss of protein absorption intensity after each cleaning step. Conclusions Our effective cleaning of explanted Prolene meshes and subsequent analyses showed that they did not degrade in vivo, confirming the in vivo stability of properly formulated polypropylene. Instead, the cracked layer that some researchers have identified as degraded Prolene is an adsorbed protein–formaldehyde coating, resulting from the well-established formalin–protein fixation process, which occurs immediately upon placing an explant in formalin.